Distinct resting-state brain activity in patients with functional constipation. (6th October 2016) - Zhu, Qiang; Cai, Weiwei; Zheng, Jianyong; Li, Guanya; Meng, Qianqian; Liu, Qiaoyun; Zhao, Jizheng; von Deneen, Karen M.; Wang, Yuanyuan; Cui, Guangbin; Duan, Shijun; Han, Yu; et al.
Highlights: The pathophysiology of functional constipation is still not completely understood. We examined the interactions of brain regions underlying functional constipation. Stronger effective connectivity from the frontal cortex propelling limbic circuit. Weaker connectivity from sensory and motor control regions to limbic circuit. Abstract: Functional constipation (FC) is a common functional gastrointestinal disorder (FGID) with a higher prevalence in clinical practice. The primary brain regions involved in emotional arousal regulation, somatic, sensory and motor control processing have been identified with neuroimaging in FGID. It remains unclear how these factors interact to influence the baseline brain activity of patients with FC. In the current study, we combined resting-state fMRI (RS-fMRI) with Granger causality analysis (GCA) to investigate the causal interactions of the brain areas in 14 patients with FC and in 26 healthy controls (HC). Our data showed significant differences in baseline brain activities in a number of major brain regions implicated in emotional process modulation (i.e. dorsal anterior cingulate cortex–dACC, anterior insula–aINS, orbitofrontal cortex–OFC, hippocampus–HIPP), somatic and sensory processing, and motor control (i.e., supplementary motor area–SMA, precentral gyrus–PreCen) ( P < 0.05, FDR correction). The GCA results revealed stronger effective connectivity from the OFC and dACC, which are regions involved with emotional regulation, propel limbic regions at the aINS and HIPP to induce abnormal emotional processing regulating visceral responses; and weaker effective connectivity from the SMA and PreCen, which are regions involved with somatic, sensory and motor control, propel the aINS and HIPP, suggesting abnormalities of sensory and behavioral responses. Such information of basal level functional abnormalities expands our current understanding of neural mechanisms underlying functional constipation.